Chemistry and our world - Gebelein, Charles G. ([S.l.] : William C Brown Pub, 1996)
Enhance your teaching efforts and foster student understanding of basic chemistry concepts and deductive reasoning using one of the most visually-oriented learning systems available. Chapter outlines, learning objectives, boxed readings, and critical thinking problems represent only a sampling of the support found within Chemistry and Our World.
Keywords: Chemistry